2021
DOI: 10.15294/lc.v16i1.29476
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Self-Efficacy Strategies in Writing Academic Papers

Abstract: This study explored the writing self-efficacy of English education undergraduates at Sanata Dharma University, Yogyakarta. Nowadays, many students still have not used self-efficacy in their studies. Consequently, they may encounter difficulties when working on tasks. As a result, the scores obtained are not the highest. Which may make them lack the motivation to learn. The purpose of this research was to determine the application of self-efficacy in writing works for the undergraduate course of English Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…Guru harus memiliki komitmen yang kuat untuk mencapai tujuan penelitian dan penulisan mereka. Untuk berhasil dalam bidang penulisan akademik, sangat penting bagi para guru untuk menunjukkan komitmen yang kuat dalam mencapai tujuan-tujuan penulisan mereka (Sumarsono & Mbato, 2021). Kompetensi ini mencakup kemampuan untuk mengatasi hambatan dan tantangan yang mungkin timbul selama proses penulisan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Guru harus memiliki komitmen yang kuat untuk mencapai tujuan penelitian dan penulisan mereka. Untuk berhasil dalam bidang penulisan akademik, sangat penting bagi para guru untuk menunjukkan komitmen yang kuat dalam mencapai tujuan-tujuan penulisan mereka (Sumarsono & Mbato, 2021). Kompetensi ini mencakup kemampuan untuk mengatasi hambatan dan tantangan yang mungkin timbul selama proses penulisan.…”
Section: Pendahuluanunclassified
“…Temuan ini sejalan dengan teori Sumarsono & Mbato (2021) yang menekankan pentingnya komitmen yang kuat bagi guru dalam mencapai tujuan penulisan akademik. Dalam teori tersebut, disoroti bahwa guru harus memiliki komitmen yang kuat untuk berhasil dalam bidang penulisan akademik.…”
Section: Goal (Menentukanunclassified
“…The fourth study conducted by Nahak & Mbato (2022) stated that both external (effective methods) and internal (self-efficacy) elements were necessary for success when reading academic content. The fifth study, conducted by Sumarsono & Mbato (2021) revealed that students with high self-efficacy will be able to read many readings from different sources. They will also find their problem-solving related to reading problems.…”
Section: Introductionmentioning
confidence: 99%
“…Writing is one of productive skills and considered as the most challenging skills to learn by the students (Oh & Lee, 2021;Sumarsono & Mbato, 2021). This is due to in writing, the students are required to go through some complex stages.…”
Section: Introductionmentioning
confidence: 99%